2020
DOI: 10.1002/chem.201905385
|View full text |Cite
|
Sign up to set email alerts
|

Cyclic Peptides as Drugs for Intracellular Targets: The Next Frontier in Peptide Therapeutic Development

Abstract: Developing macrocyclic peptides that can reach intracellular targets is a significant challenge. This review discusses the most recent strategies used to develop cell permeable cyclic peptides that maintain binding to their biological target inside the cell. Macrocyclic peptides are unique from small molecules because traditional calculated physical properties are unsuccessful for predicting cell membrane permeability. Peptide synthesis and experimental membrane permeability is the only strategy that effective… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
94
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 122 publications
(111 citation statements)
references
References 160 publications
0
94
0
Order By: Relevance
“…Cyclic head-to-tail peptides occur in a wide variety of natural products, with an impressive range of biological activities [ 56 , 57 ]. These cyclic peptides generally improve metabolic stability and may improve structural rigidity due to the geometric preorganization into a suitable conformation for binding.…”
Section: 123- Triazole Moiety and Peptide Structurementioning
confidence: 99%
“…Cyclic head-to-tail peptides occur in a wide variety of natural products, with an impressive range of biological activities [ 56 , 57 ]. These cyclic peptides generally improve metabolic stability and may improve structural rigidity due to the geometric preorganization into a suitable conformation for binding.…”
Section: 123- Triazole Moiety and Peptide Structurementioning
confidence: 99%
“…A recent study demonstrated modulation of scaffold rigidity to engineer favorable ADME properties in macrocyclic peptides (Furukawa et al, 2020). Finally, drug design strategies, such as N-methylation or replacing NH with sulfur (or vice versa), were found to improve pharmacological activity, solubility, and/or permeability of macrocycles (Mallinson and Collins, 2012;Liras and McClure, 2019;Stadelmann et al, 2020;Buckton et al, 2021). Extending studies of this nature to macrocyclic hybrids is expected to improve their oral bioavailability for systemic uses.…”
Section: Limitations and Ways Forward In Macrocycle-antibiotic Hybrid Approachmentioning
confidence: 99%
“… 15 Alternative approaches for creating cell-permeable peptides to disrupt p53/MDMX interactions using cyclic peptide scaffolds, 16 polycationic tags or medchem optimization strategies have been extensively studied. 17,18 …”
Section: Introductionmentioning
confidence: 99%